Hubungan Paparan Asap Rokok Dengan Pneumonia Pada Anak Usia 1-4 Tahun - Sari, Kartika; Eppang, Yudiarsi (Karya Kesehatan Siwalima, 2025)
Pneumonia is an acute respiratory infection and a leading cause of child mortality worldwide, with exposure to cigarette smoke identified as one of its risk factors. This study aims to determine the relationship between exposure to cigarette smoke and the incidence of pneumonia in children aged 1–4 years at RSUD dr. La Palaloi Maros. A descriptive analytic design with a cross-sectional approach was used, involving 55 children diagnosed with pneumonia based on medical record data and selected through total sampling. The results showed that most pneumonia cases occurred in children aged 1–2 years (62.5%) and were more common in boys (65.0%). Among the 40 children diagnosed with pneumonia, 35 (63.61%) were exposed to cigarette smoke. Statistical analysis using the Chi-Square test indicated a significant association between exposure to cigarette smoke and the incidence of pneumonia (p = 0.000). This study concludes that cigarette smoke exposure is significantly associated with pneumonia in children aged 1–4 years. It is therefore recommended that parents create a healthier home environment by avoiding smoking indoors as a preventive measure.